Gender Politics and Political Strategies of Female Candidate in Lampung Province, Indonesia - Muhadam Labolo; Hasna Azmi Fadhilah; Teguh Ilham (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2021)
Female politicians in Indonesia still facing social discrimination when running for election, both in being a regional leader or legislative member. Some of them had succeeded in overcoming those challenges, while others find it difficult. This article figured out the implemented strategy by the female political candidate in Lampung when facing social discrimination during her candidacy. This case study used deep interviews with prominent figures, observation, and documentation. The result showed that the female candidate in the Lampung governor election maximized her social networks, apart from other factors that helped her win the election with her political pair. To overcome social barriers and discrimination, a female political candidate should use many strategies, including the extensive use of social media to win the majority of votes.